An Analysis of Students’ Difficulties in Writing Narrative Text - Nandha Amelya; Samtidar Samtidar; Sultan Baa (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2022)
This study aims to find out the difficulties were experienced by the students in writing narrative text. This study used descriptive qualitative method. To achieve the research objectives, researchers used written test and interview as the instruments in collecting the data. The subjects of this study were students of XI IPS 1 in SMAN 5 Bone, there were 26 students as the participants and there were six students as the respondent of the interview. This study used random sampling technique to determine the subject of research. Based on the results of the study, the researchers found that difficulties were experienced by the Eleventh-grade students of SMAN 5 Bone are classified into psychological difficulties, linguistic difficulties, and cognitive difficulties. Psychological difficulties were experienced by the students are low confidence, low motivation, and writing anxiety. They also experienced difficulties in four writing aspects, there are; vocabulary and language use which are classified into linguistic difficulties, content and mechanic which are classified into cognitive difficulties. Then, the most difficulties that happened to the students when writing narrative text are vocabulary and language use aspect. The students still had limited vocabulary. They also are less knowledge about English grammatical. In accordance to those difficulties, students also have internal problems; writing anxiety, low confidence and motivation.